Repeat proliferation and partial endoreplication jointly shape the patterns of genome size evolution in orchids. (25th May 2021) - Chumová, Zuzana; Záveská, Eliška; Hloušková, Petra; Ponert, Jan; Schmidt, Philipp‐André; Čertner, Martin; Mandáková, Terezie; Trávníček, Pavel
Summary: Although the evolutionary drivers of genome size change are known, the general patterns and mechanisms of plant genome size evolution are yet to be established. Here we aim to assess the relative importance of proliferation of repetitive DNA, chromosomal variation (including polyploidy), and the type of endoreplication for genome size evolution of the Pleurothallidinae, the most species‐rich orchid lineage. Phylogenetic relationships between 341 Pleurothallidinae representatives were refined using a target enrichment hybrid capture combined with high‐throughput sequencing approach. Genome size and the type of endoreplication were assessed using flow cytometry supplemented with karyological analysis and low‐coverage Illumina sequencing for repeatome analysis on a subset of samples. Data were analyzed using phylogeny‐based models. Genome size diversity (0.2–5.1 Gbp) was mostly independent of profound chromosome count variation (2 n  = 12–90) but tightly linked with the overall content of repetitive DNA elements. Species with partial endoreplication (PE) had significantly greater genome sizes, and genomic repeat content was tightly correlated with the size of the non‐endoreplicated part of the genome. In PE species, repetitive DNA is preferentially accumulated in the non‐endoreplicated parts of their genomes. Our results demonstrate that proliferation of repetitive DNA elements and PE together shape the patterns of genome size diversity in orchids. Significance Statement: A unique feature of orchids that remains poorly understood is partial endoreplication (PE), a form of endopolyploidy resulting in multiplication of only a fraction of the genome in the course of cell differentiation. Using repeatome analysis within a novel evolutionary frame, we investigated the linkage between PE and genome size evolution in Pleurothallidinae orchids, and showed that proliferation of repetitive elements in PE species enlarges mainly the non‐endoreplicated part of the genome.